2022
DOI: 10.3389/fpls.2022.889370
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted LC–MS/MS-Based Metabolomic Profiling for the Edible and Medicinal Plant Salvia miltiorrhiza Under Different Levels of Cadmium Stress

Abstract: Salvia miltiorrhiza, a medicinal and edible plant, has been extensively applied to treat cardiovascular diseases and chronic hepatitis. Cadmium (Cd) affects the quality of S. miltiorrhiza, posing serious threats to human health. To reveal the metabolic mechanisms of S. miltiorrhiza's resistance to Cd stress, metabolite changes in S. miltiorrhiza roots treated with 0 (CK), 25 (T1), 50 (T2) and 100 (T3) mg kg−1 Cd by liquid chromatography coupled to mass spectrometry (LC–MS/MS) were investigated. A total of 305 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…The synthesis and release of unsaturated fatty acids is a plant defense mechanism against abiotic stresses [52]. Salvia miltiorrhiza downregulates unsaturated fatty acids (oleic acid, linoleic acid) and upregulates saturated fatty acids (stearic acid) under Cd stress [53]. However, the unsaturated fatty acid contents (linoleic, 13-hydroperoxy-9z,11e-octadecadienoic acid) increased with increasing Cd concentration in S. tonkinensis, consistent with previously reported results [54].…”
Section: Role Of Fatty Acids Under CD Stresssupporting
confidence: 89%
“…The synthesis and release of unsaturated fatty acids is a plant defense mechanism against abiotic stresses [52]. Salvia miltiorrhiza downregulates unsaturated fatty acids (oleic acid, linoleic acid) and upregulates saturated fatty acids (stearic acid) under Cd stress [53]. However, the unsaturated fatty acid contents (linoleic, 13-hydroperoxy-9z,11e-octadecadienoic acid) increased with increasing Cd concentration in S. tonkinensis, consistent with previously reported results [54].…”
Section: Role Of Fatty Acids Under CD Stresssupporting
confidence: 89%
“…In plants, amino acids can effectively chelate metal ions in the cytoplasm to reduce the toxic effect of heavy metals on plants (Singh et al, 2016). L-Glutamate is an intermediate for the biosynthesis of oxidized amino acids, which plants can use for secondary metabolisms, such as the biosynthesis of glutamine, proline, and lysine (Yuan et al, 2022b). Glutamine is an essential precursor of glutathione biosynthesis in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aminoacyl-tRNA biosynthesis was significantly enriched in all four comparisons, and only the MT treatment significantly increased the expression levels of L-isoleucine, L-arginine, Lhistidine and L-tyrosine (Figures 3, 4D acids, as essential compounds for plant growth, play an important role in physiological metabolism, such as plant nutrition and resistance to Cd toxicity. Studies have shown that accumulation of L-aspartic acid alleviates the toxicity of Cd to Salvia miltiorrhiza, 19 and exogenous L-glutamic acid can reduce oxidative damage and inhibit Cd accumulation in Lens culinaris Medik. 44 Meanwhile, ABC transporters can also maintain cellular osmotic homeostasis by regulating the uptake and transport of secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Brassica napus (CB671) can improve Cd tolerance through cell wall polysaccharides, lignin accumulation and the synthesis of antioxidant substances such as anthocyanins . Amino acids ( dl -tryptophan, l -aspartic acid, l -proline, L serine, and l -histidine), organic acids (eudesmic acid and chorismate) and fatty acids (oleic acid, linoleic acid, and stearic acid) in the roots of Salvia miltiorrhiza play an important role in the resistance to Cd toxicity . Lapie et al applied LC–MS and GC–MS and found that with increasing Cd toxicity, the total carbon, sugar, and amino acids in maize root exudates and mucilage decreased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation